PENYELESAIAN SENGKETA ASET DAERAH ANTARA PEMERINTAH PROVINSI RIAU DENGAN PEMERINTAH KOTA PEKANBARU TAHUN 2019-2021 - Telaumbanua, Mesra Damai; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Regional assets that should be a weapon to boost the movement of an effective and efficient government system, but this has not been realized due to identity issues regarding these assets between the Pekanbaru City Government and the Riau Provincial Government. Some assets are not used effectively because both parties have the same authority over these assets. With these problems, a study was conducted to describe how to resolve regional asset disputes between the Pekanbaru City Government and the Riau Provincial Government in 2019-2021. This study uses Garry Goopaster's theory, namely dispute resolution through mediation. The data collection techniques used are interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions or verification. The results of the study show that the resolution of regional asset disputes between the Pekanbaru City Government and the Provincial Government takes quite a long time, many of which are considered due to changes in the rules regarding the management of regional assets, coupled with the Covid situation that hit Indonesia, especially Riau Province. With various dynamics, finally the problem between the Pekanbaru City Government and the Riau Provincial Government was resolved through mediation. Assets were donated from the Riau Provincial Government to the Pekanbaru City Government. Keyword: Dispute Resolution, Regional Assets, Local Government